1994
DOI: 10.1037/0022-0167.41.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Presenting problems of university counseling center clients: A snapshot and multivariate classification scheme.

Abstract: A multivariate categorization scheme for classifying clients' presenting problems was empirically developed. Six hundred and eleven clients who sought services at a university counseling center completed the Computerized Assessment System for Psychotherapy Evaluation and Research (L. McCullough & A. D. Farrell, 1983). Descriptive statistics, cluster analysis, cluster differentiation by external variables, and stability of cluster solutions across subsamples are presented. Nine clusters of clients with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 40 publications
6
51
0
1
Order By: Relevance
“…During the most recent period assessed (1996)(1997)(1998)(1999)(2000)(2001), the percentage of students presenting for treatment who reported physical abuse, sexual assault, and substance abuse was 12, 3.5, and 7%, respectively. A cluster analysis of 611 counseling center clients assessed in 6 areas of functioning (suicidality, thought disorders, physical problems, interpersonal problems, mood problems, and leisure activity impairment), 10% had significant impairment in all areas and 8% had problems with substance use (Heppner, Kivlighan, Good, Roehlke, Hills, & Ashby, 1994), a finding replicated by a subsequent study of 6 years of intake information (Pledge, Lapan, Heppner, Kivlighan, & Roehlke, 1998).…”
Section: Implications For Counseling Centersmentioning
confidence: 56%
“…During the most recent period assessed (1996)(1997)(1998)(1999)(2000)(2001), the percentage of students presenting for treatment who reported physical abuse, sexual assault, and substance abuse was 12, 3.5, and 7%, respectively. A cluster analysis of 611 counseling center clients assessed in 6 areas of functioning (suicidality, thought disorders, physical problems, interpersonal problems, mood problems, and leisure activity impairment), 10% had significant impairment in all areas and 8% had problems with substance use (Heppner, Kivlighan, Good, Roehlke, Hills, & Ashby, 1994), a finding replicated by a subsequent study of 6 years of intake information (Pledge, Lapan, Heppner, Kivlighan, & Roehlke, 1998).…”
Section: Implications For Counseling Centersmentioning
confidence: 56%
“…Clarification in this matter is critical, as researchers, such as Corazzini (1997), have noted that not enough attentions have been given to how the increasing level of pathology among college students seeking mental health services relates to the growing diversity in demographics present among university populations. Heppner et al (1994) revealed in their study that the variable of client ethnicity was strongly associated with higher levels of distress, demonstrating the pressure related to being a member of a minority group within a predominantly white institution and the possible reluctance to use counseling services, unless levels of stress become more intense. To complicate matters, discrepancies between the level of students' reported distress and students' actual distress have been cited in the literature (Kelley, Kahn, & Coulter, 1996;Solberg, Ritsma, Davis, & Tata, 1994).…”
Section: The Mcci: Operationalizing Assessment To Treatmentmentioning
confidence: 99%
“…Other well-established assessment measures, such as the BDI (Beck Depression Inventory), the SCL-90-R (Symptom Checklist-90-Revised), the BSI (Brief Symptom Inventory) and the Mooney Problem Checklist, have shown to have some limitations when utilized in college counseling settings (Hayes, 1997;Hayes & Mahalik, 2000;Heppner, Kivlighan, Good, Roehlke, Hills, & Ashby, 1994;Svanum & Zody, 2001;Todd, Deane, & Mckenna, 1997). They used a univariate approach and collecting data primarily from mid-Western, predominantly Caucasian universities, with questionable results regarding of the reliability and validity of a culturally and ethnical diverse student body (Hayes, 1997;Hayes & Mahalik, 2000;Todd et al, 1997;Svanum & Zody, 2001;Heppner et al, 1994).…”
Section: The Mcci: Operationalizing Assessment To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although low coefficients were typically found for categories with a small number of items, the mean alpha coefficient for eight categories with more than four items was .69. Heppner et al (1994) examined the structure of seven rationally derived scales composed of CASPER items in a sample of 611 clients at a university counseling center. This analysis was restricted to CASPER items that assessed frequency of problems within the past 30 days.…”
mentioning
confidence: 99%